Pengaruh Budaya Organisasi, Kepuasan Kerja, dan Gaya Kepemimpinan terhadap Motivasi Kerja Karyawan pada Hotel Mega Anggrek Jakarta di Masa Pandemi Covid 19 - Clariza Febriandiny; Renny Husniati (Owner : Riset dan Jurnal Akuntansi, 2022)
This study aims to understand and demonstrate the influence of organizational culture, job satisfaction, and leadership style on employee work motivation at Mega Anggrek Hotel Jakarta during the Covid 19 pandemic. The sampling technique used was Non Probability Sampling with a saturated sample type. Assistance applications when processing data using SmartPLS 3.0 by performing T-test and F-test, so that the output results can be known and statistically proven that: (1) Organizational Culture has a positive and significant effect on employee motivation, (2) Job Satisfaction has a positive and significant effect on significant effect on work motivation (3) leadership style has a negative and significant effect on work motivation, (4) organizational culture, job satisfaction, and leadership style have a joint and significant effect on work motivation.